Aminoglycoside Antibiotics Inhibit Phage Infection by Blocking an Early Step of the Infection Cycle - Kever, Larissa; Hardy, Aël; Luthe, Tom; Hünnefeld, Max; Gätgens, Cornelia; Milke, Lars; Wiechert, Johanna; Wittmann, Johannes; Moraru, Cristina; Marienhagen, Jan; Frunzke, Julia (mBio, 2022)
Predation by phages is a major driver of bacterial evolution. As a result, elucidating antiphage strategies is crucial from both fundamental and therapeutic standpoints. In response to viral predation, bacteria have evolved a wide range of defense mechanisms, which rely mostly on proteins acting at the cellular level. Here, we show that aminoglycosides, a well-known class of antibiotics produced by Streptomyces , are potent inhibitors of phage infection in widely divergent bacterial hosts. We demonstrate that aminoglycosides block an early step of the viral life cycle, prior to genome replication. Phage inhibition was also achieved using supernatants from natural aminoglycoside producers, indicating a broad physiological significance of the antiviral properties of aminoglycosides. Strikingly, we show that acetylation of the aminoglycoside antibiotic apramycin abolishes its antibacterial effect but retains its antiviral properties. Altogether, our study expands the knowledge of aminoglycoside functions, suggesting that aminoglycosides not only are used by their producers as toxic molecules against their bacterial competitors but also could provide protection against the threat of phage predation at the community level. IMPORTANCE Predation by phages is a major driver of bacterial evolution. As a result, elucidating antiphage strategies is crucial from both fundamental and therapeutic standpoints. While protein-mediated defense mechanisms, like restriction-modification systems or CRISPR/Cas, have been extensively studied, much less is known about the potential antiphage activity of small molecules. Focusing on the model bacteria Escherichia coli and Streptomyces venezuelae , our findings revealed significant antiphage properties of aminoglycosides, a major class of translation-targeting antibiotics produced by Streptomyces . Further, we demonstrate that supernatants from natural aminoglycoside producers protect bacteria from phage propagation, highlighting the physiological relevance of this inhibition. Suppression of phage infection by aminoglycosides did not result from the indirect inhibition of bacterial translation, suggesting a direct interaction between aminoglycosides and phage components. This work highlights the molecular versatility of aminoglycosides, which have evolved to efficiently block protein synthesis in bacterial competitors and provide protection against phages.